2012
DOI: 10.2310/8000.2012.110631
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral occult hip fracture

Abstract: One of the most common acute injuries seen in the emergency department is the hip fracture. This injury is usually diagnosed by plain radiographs, however these fractures are sometimes not obviously apparent. Occult hip fractures present a pitfall for emergency department physicians. We present a case of a patient who sustained bilateral occult hip fractures. We review the epidemiology of the condition, examine what diagnostic studies are available that may help the physician avoid missing the occult hip fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Almost all hip fractures presenting to the emergency department are diagnosed by routine plain X-rays. 26 However, an undiagnosed occult ITF fracture can lead to risk of displacement, longer hospital stay, and delayed ambulation. 27,28 Therefore, the necessity of surgical treatment may occur in a GT fracture that seems simple on plain radiography.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all hip fractures presenting to the emergency department are diagnosed by routine plain X-rays. 26 However, an undiagnosed occult ITF fracture can lead to risk of displacement, longer hospital stay, and delayed ambulation. 27,28 Therefore, the necessity of surgical treatment may occur in a GT fracture that seems simple on plain radiography.…”
Section: Discussionmentioning
confidence: 99%
“…In the emergency department, most hip fractures are diagnosed based on a routine radiograph [ 2 , 24 ]. However, missing the diagnosis of an occult intertrochanteric fracture may lead to fracture displacement, unnecessary surgery, longer hospitalization time, and delayed rehabilitation [ 2 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pandey et al conducted an ER based study evaluating patients with traumatic hip pain and negative X-rays by MRI. They identified 22 fractures out of 33 suspected cases, but did not provide a total number of hip fractures for the period [ 21 ]. Dominguez et al found 4.4 % of patients with hip trauma and negative X-rays had a hip or pelvic fracture identified by MRI, representing 9.9 % of the total number of hip fractures [ 4 ].…”
Section: Discussionmentioning
confidence: 99%